Pemanfaatan Media Pembelajaran Audio Visual Berbasis Aplikasi Canva dalam Meningkatkan Kemampuan Basic Desain Grafis Siswa di Sekolah Dasar - Quraniyah, Risa Lailatul; Fidrayani, Fidrayani (Lembaga Yasin AlSys, 2024)
Although audiovisual media has been widely used in the learning process, research on the effectiveness of using Canva to enhance elementary students' graphic design skills remains limited. This gap indicates the need for more in-depth studies to understand how the Canva application can influence students' creativity and engagement in the context of primary education. The purpose of this study is to identify how audiovisual media can attract elementary students to graphic design through Canva. The method used in this research is a Systematic Literature Review (SLR). The aspects discussed in this study include the title, abstract, introduction, method, results, discussion, and conclusion. The data collected comprises relevant articles from several sources from 2019 to 2024 related to the topic of using Canva-based audiovisual learning media to improve students' basic graphic design skills. The method used is a Systematic Literature Review (SLR), which includes the analysis of various relevant journal articles. The results of the study indicate that the use of Canva can enhance students' creativity, engagement, and technical skills in graphic design. In the first cycle, students showed a significant improvement in basic skills, and in the second cycle, there was further improvement with higher completeness. Using Canva as a learning medium has proven effective in enhancing students' graphic design competence, while also encouraging them to be more explorative and creative.